Tonga : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper assesses the fiscal risk impact of various events in Tonga and describes the challenges implied for fiscal management. The paper discusses that the Tongan government has made various efforts to limit the budgetary implications of the recent economic and political shocks, including pursuing revenue administration efforts, cutting other expenditures, and seeking donor assistance. The paper examines rising household indebtedness in Tonga. Within the framework of the life-cycle hypothesis, the paper finds that Tonga's relatively young demographic distribution tends to be associated with higher level of aggregate household debt.